The Youth Olympic Games: Past, present and future - Wong, D. (The International Journal of the History of Sport, 2012)
Hailed as the flagship of the International Olympic Committee (IOC) strategy regarding young people, the organising of the Youth Olympic Games (YOG) was approved by the IOC in 2007 and Singapore was subsequently selected as the first host city for the summer YOG. Although the YOG is going to be the first new event the IOC has staged since the 1924 winter Olympic Games, its novelty may not be as radical as first impressions may suggest. This paper charts the chronological development of the YOG through a broad overview of little-known Youth Olympic Festivals, which the YOG is reported to be modelled after, and traces the political/economical/ideological contexts for the conception of the YOG. Despite being the latest addition to the Olympics family, the YOG is not spared from conflicts and tensions which inundated the Olympic Games. This paper aims to exemplify the range of debates presented by the launch of the YOG and contribute to the literature examining the opportunities and challenges presented by the launch of the YOG. In der auf junge Menschen zielenden Strategie des Internationalen Olympischen Komitees (IOC) wurden die Youth Olympic Games (YOG) als Aushängeschild gepriesen. Ihre Ausrichtung wurde 2007 beschlossen und Singapur als erster Austragungsort gewählt. Obwohl die YOG die erste neue Veranstaltung des IOCs seit der Einführung der Winterspiele 1924 sind, sind sie dennoch nicht so bahnbrechend neu wie es der erste Anschein erwecken mag. Dieser Beitrag zeichnet die chronologische Entwicklung der YOG durch einen umfassenden Überblick über die eher unbekannten Youth Olympic Festivals nach, denen die YOG nachempfunden sein sollen, und beleuchtet die politischen, ökonomischen sowie ideologischen Hintergründe, die der Konzeption der YOG zugrunde liegen. Obwohl die YOG das jüngste Mitglied der Olympischen Familie sind, sind auch sie Objekt der Konflikte und Spannungen, die die Olympischen Spiele begleiten. Diese Abhandlung erläutert die Bandbreite der Diskussionen bei der Einführung der YOG und soll ein Beitrag zu jener Literatur sein, die sich mit den Möglichkeiten und Herausforderungen der Einführung der YOG beschäftigt.